2020
DOI: 10.1089/dia.2019.0286
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Performance of the Omnipod Hybrid Closed-Loop System in Adults, Adolescents, and Children with Type 1 Diabetes Over 5 Days Under Free-Living Conditions

Abstract: Background: The objective of this study was to assess the safety and performance of the Omnipod Ò personalized model predictive control (MPC) algorithm in adults, adolescents, and children aged ‡6 years with type 1 diabetes (T1D) under free-living conditions using an investigational device. Materials and Methods: A 96-h hybrid closed-loop (HCL) study was conducted in a supervised hotel/rental home setting following a 7-day outpatient standard therapy (ST) phase. Eligible participants were aged 6-65 years with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
1
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 39 publications
1
38
1
6
Order By: Relevance
“…very small boluses are delivered every few minutes. 19 However, in a recent artificial pancreas study satisfactory glycemic control could be shown with OP 20 suggesting that feedback control may be able to compensate for inaccuracy and variance in insulin delivery. Occlusion detection is a safety mechanism of insulin pumps and alarmingly, is not as reliable as one would expect.…”
Section: Discussionmentioning
confidence: 99%
“…very small boluses are delivered every few minutes. 19 However, in a recent artificial pancreas study satisfactory glycemic control could be shown with OP 20 suggesting that feedback control may be able to compensate for inaccuracy and variance in insulin delivery. Occlusion detection is a safety mechanism of insulin pumps and alarmingly, is not as reliable as one would expect.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies, using a variety of systems with varying algorithms, pump, and sensors, have been performed in adults and children (163)(164)(165)(166)(167)(168)(169)(170)(171)(172)(173). Evidence suggests such systems may reduce A1C levels and improve time in range (174)(175)(176)(177)(178). They may lower the risk of exerciserelated hypoglycemia (179) and may have psychosocial benefits (180)(181)(182)(183).…”
Section: Insulin Pumps In Patients With Type 2 and Other Types Of Diamentioning
confidence: 99%
“…In a randomized crossover trial, an increase of 9.2% of the time spent in the target was observed using this AP [122], and performances were evaluated also in more challenging situations as meals and physical exercise [123]. The Omnipod Horizon system [124] uses a patch pump and both its safety and efficacy were demonstrated in both adults and pediatric T1Ds even also in an outpatient setting [125,126]. CLCs equally allow a better QoL, by reducing the burden related to diabetes by demonstrating a significant reduction of the time spent in diabetes management [127,128].…”
Section: Artificial Pancreasmentioning
confidence: 99%